2019
DOI: 10.3168/jds.2019-16412
|View full text |Cite
|
Sign up to set email alerts
|

Classifying the fertility of dairy cows using milk mid-infrared spectroscopy

Abstract: The objective of this study was to investigate the potential of milk mid-infrared (MIR) spectroscopy, MIR-derived traits including milk composition, milk fatty acids, and blood metabolic profiles (fatty acids, β-hydroxybutyrate, and urea), and other on-farm data for discriminating cows of good versus poor likelihood of conception to first insemination (i.e., pregnant vs. open). A total of 6,488 spectral and milk production records of 2,987 cows from 19 commercial dairy herds across 3 Australian states were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…The authors concluded that pregnant versus open cows post insemination could be discriminated with promising accuracy using milk spectra, parity, and days in milk. Ho et al (2019) reported that milk spectra from early lactation cow together with other on-farm data (e.g., days in milk, days from calving to insemination, calving age, milk yield, genotypes, among others) could be used to classify cows that conceived at first insemination or did not conceive within the breading season with reasonable accuracy, based on the area under the curve (0.75), in herd-by-herd external validation. Delhez et al (2020) observed that milk spectra recorded after 150 days of pregnancy was promising to predict the pregnancy status in Holstein, with the area under the curve around 0.76 in cowindependent external validation.…”
Section: Fertilitymentioning
confidence: 99%
“…The authors concluded that pregnant versus open cows post insemination could be discriminated with promising accuracy using milk spectra, parity, and days in milk. Ho et al (2019) reported that milk spectra from early lactation cow together with other on-farm data (e.g., days in milk, days from calving to insemination, calving age, milk yield, genotypes, among others) could be used to classify cows that conceived at first insemination or did not conceive within the breading season with reasonable accuracy, based on the area under the curve (0.75), in herd-by-herd external validation. Delhez et al (2020) observed that milk spectra recorded after 150 days of pregnancy was promising to predict the pregnancy status in Holstein, with the area under the curve around 0.76 in cowindependent external validation.…”
Section: Fertilitymentioning
confidence: 99%
“…We followed the same approach as Ho et al (2019), but applied to additional data that were added to the data set used by Ho et al (2019) specifically to address the question of whether the model could be validated in a commercial setting where the outcome of mating is unknown. Between 2016 and 2018 inclusive, commercial farmer records, collected by several milk recording organizations, of insemination date, calving date, DIM at herd-test, DAI, age at calving (i.e., interval between birth date and calving date), herd-test day milk yield (MY), fat, protein, and lactose percentages, SCC, calving season (i.e., spring, summer, autumn, and winter), and MIR spectroscopy were obtained from DataGene (https: / / www .datagene .com .au/ ) for 9,850 lactating cows (33,483 records) from 29 commercial dairy herds located in Victoria, Tasmania, and New South Wales of Australia.…”
Section: Animal Datamentioning
confidence: 99%
“…The models currently available for predicting fertility of dairy cows use data from different sources, ranging from comparatively difficult to measure (e.g., BW and BCS), to moderately easy to measure (e.g., milk progesterone) or easy to measure [e.g., milk production, milk composition, and milk mid-infrared (MIR) spectroscopy] (Shahinfar et al, 2014;Hempstalk et al, 2015;Cook and Green, 2016;Blavy et al, 2018;Ho et al, 2019). Among these models, some use early-lactation milk-recording data (e.g., milk production, milk composition, and MIR spectroscopy), which is a pragmatic approach because this information is readily accessible for most dairy farms, and therefore, it would not add too much cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…55,56,60 More recently, mid-infrared (MIR) spectroscopy of milk has shown promise for assessing more complex animal health traits. 27,[61][62][63] It is established that MIR spectral data can be used to screen for subclinical ketosis through identification of ketone bodies in milk 64 and to estimate energy balance in early lactation. 65…”
Section: Evaluation Of Hypocalcemiamentioning
confidence: 99%